2017
DOI: 10.3390/ijerph14121577
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Albuminuria in Children Living in a Rural Agricultural and Fishing Subsistence Community in Lake Chapala, Mexico

Abstract: The occurrence of Chronic Kidney Disease (CKD) of unknown etiology in autochthonous child populations residing along the Lake Chapala lakeshore is endemic (Jalisco, México). The objective of this study was to determine the prevalence of albuminuria in the pediatric population and to measure the glomerular filtration rate in children with two positive albuminuria tests. Urinary albumin was measured in 394 children. Subjects with two or more positive albuminuria test donated blood samples for the determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
11
1
Order By: Relevance
“…Kidney disease is more prevalent in adults from these communities than in those from other Jalisco municipalities -CKD, 20.1% versus 10.4%; proteinuria, 36.1% versus 11.0%. Similar findings were reported for children 194,195 . Unsafe drinking water, poor sanitation and contamination of the lake and water wells are likely risk factors.…”
Section: Box 3 | Water Sanitation and Ckd In Jalisco Mexicosupporting
confidence: 90%
“…Kidney disease is more prevalent in adults from these communities than in those from other Jalisco municipalities -CKD, 20.1% versus 10.4%; proteinuria, 36.1% versus 11.0%. Similar findings were reported for children 194,195 . Unsafe drinking water, poor sanitation and contamination of the lake and water wells are likely risk factors.…”
Section: Box 3 | Water Sanitation and Ckd In Jalisco Mexicosupporting
confidence: 90%
“…In children, although the prevalence of CKD was similar to other Jalisco municipalities, the prevalence of proteinuria was 10 times higher [16]. Similarly, a recent cross-sectional study in children residing in these communities reported a prevalence of albuminuria and CKD of 45% and 33%, respectively; these rates of albuminuria are 3-5 times higher than reported in the state of Jalisco and the international literature [17]. Information from Jalisco's vital statistics shows a high prevalence of intestinal infection, associated with a high mortality rate among children under 5 years of age [10].…”
Section: Introductionmentioning
confidence: 64%
“…Since 2016, the Department of Public Health of the University of Guadalajara has carried out studies in the zone, specifically in the community of Agua Caliente, Poncitlán Municipality, State of Jalisco. In this community, health problems have been detected such as malnutrition and albuminuria, specifically in children and adolescents under the age of 17 years [7].…”
Section: Methodsmentioning
confidence: 99%